Measurement of the W boson polarisation in tt[bar] events from pp collisions at √s = 8 TeV in the lepton + jets channel with ATLAS - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Baas, Alessandra Edda; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; et al. (The European physical journal. C, Particles and fields, 2017)
This paper presents a measurement of the polarisation of W bosons from tt¯ decays, reconstructed in events with one high-p T lepton and at least four jets. Data from pp collisions at the LHC were collected at s√ = 8 TeV and correspond to an integrated luminosity of 20.2 fb−1. The angle θ∗ between the b-quark from the top quark decay and a direct W boson decay product in the W boson rest frame is sensitive to the W boson polarisation. Two different W decay products are used as polarisation analysers: the charged lepton and the down-type quark for the leptonically and hadronically decaying W boson, respectively. The most precise measurement of the W boson polarisation via the distribution of cosθ∗ is obtained using the leptonic analyser and events in which at least two of the jets are tagged as b-quark jets. The fitted fractions of longitudinal, left- and right-handed polarisation states are F0= 0.709 ± 0.019, FL= 0.299 ± 0.015 and FR= −0.008 ± 0.014, and are the most precisely measured W boson polarisation fractions to date. Limits on anomalous couplings of the Wtb vertex are set.
Gesehen am 11.02.2020
Im Titel steht der Buchstabe "s" unter dem Wurzelsymbol
Im Titel steht jeweils der 2. Buchstabe t mit einem Oberstrich
*ATLAS Collaboration: M. Aaboud, C.F. Anders, V. Andrei, C. Antel, A.E. Baas, O. Brandt, J.J. Djuvsland, M. Dunford, D.E. Ferreira de Lima, M.P. Geisler, M. Giulini, P. Hanke, J. Jongmanns, E.-E. Kluge, M. Kolb, M. Kretz, A. Kugel, V.S. Lang, M. Lisovyi, K. Meier, H. Meyer zu Theenhausen, D.I. Narrias Villar, M. Sahinsoy, S. Schaetzel, V. Scharf, A. Schoening, H.-C. Schultz-Coulon, D. Sosa, R. Stamen, P. Starovoitov, S. Suchek, M. Wessels [und 2818 weitere Personen]